2011
DOI: 10.1177/1475921711414231
|View full text |Cite
|
Sign up to set email alerts
|

Development of a triboluminescence-based sensor system for concrete structures

Abstract: The triboluminescence phenomenon has been proposed as a sensor system for detecting and monitoring damage in aerospace and civil infrastructure systems (CIS). While significant work is being done in developing such systems for aerospace structures, little or no work is being done in developing triboluminescence-based sensor systems for the critical and aging CIS. This article reports some findings in the work being done by the authors to develop such a sensor system for civil infrastructure applications. A ZnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…At this point, it is noteworthy to point out that this new technique shows the possibility to characterize the structural integrity of large structural health monitoring systems (SHMS) in case that the ML material is used as an artificial skin in form of ML paint, patch, or thin film, although further studies will be needed to verify the effect of the crack speed quantitatively on the basis of the exact ML solution under dynamic condition. Considering that failure of engineering structures mainly arises from the expansion of micro or macrocracks inherent in the applied materials under operational environments, tracing the whole evolution of all cracks and instantaneously evaluating their significance would be the essential requirement for SHMS . With this regard, the use of the ML technology could be one of the possible substitutive and substantial methods for SHMS due to its relative simplicity but effectiveness in detecting arrested or propagating crack tips and assessing the in situ structural state by means of fracture parameters, such as SIFs determined from the cumulative ML fringe patterns in front of static or dynamic cracks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is noteworthy to point out that this new technique shows the possibility to characterize the structural integrity of large structural health monitoring systems (SHMS) in case that the ML material is used as an artificial skin in form of ML paint, patch, or thin film, although further studies will be needed to verify the effect of the crack speed quantitatively on the basis of the exact ML solution under dynamic condition. Considering that failure of engineering structures mainly arises from the expansion of micro or macrocracks inherent in the applied materials under operational environments, tracing the whole evolution of all cracks and instantaneously evaluating their significance would be the essential requirement for SHMS . With this regard, the use of the ML technology could be one of the possible substitutive and substantial methods for SHMS due to its relative simplicity but effectiveness in detecting arrested or propagating crack tips and assessing the in situ structural state by means of fracture parameters, such as SIFs determined from the cumulative ML fringe patterns in front of static or dynamic cracks.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that failure of engineering structures mainly arises from the expansion of micro or macrocracks inherent in the applied materials under operational environments, tracing the whole evolution of all cracks and instantaneously evaluating their significance would be the essential requirement for SHMS. 45,46 With this regard, the use of the ML technology could be one of the possible substitutive and substantial methods for SHMS due to its relative simplicity but effectiveness in detecting arrested or propagating crack tips and assessing the in situ structural state by means of fracture parameters, such as SIFs determined from the cumulative ML fringe patterns in front of static or dynamic cracks. Given the additional prominent features of the ML technology, such as being a whole-field reaction, having a short response time, representing a noncontacting measurement, and exhibiting cost effectiveness, etc., this newly suggested theoretical and empirical method for the evaluation of conventional fracture could be considered as one of breakthroughs in the research field of ML-based structural diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed to harness the TL emission within composite materials to sense damage [8,9]. Much research has been done to develop an in situ, wireless damage-sensing component for composite materials [10][11][12]. One major concern during developing a triboluminescence-based damage-sensing device is whether the TL emission is of a great enough intensity to be properly recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper reports the FML of the ZnS:Mn phosphor and attempts to solve the two problems related to the dominating mechanism of ML and impact velocity dependence of ML in the ZnS:Mn phosphor. The study of ML of ZnS:Mn phosphor is meaningful, as recent studies have shown that ZnS:Mn phosphor has the potential for use in sensors for the detection of damage in structures using ML and ML structural health monitoring systems .…”
Section: Introductionmentioning
confidence: 99%